FLIPPED CLASSROOM APPROACH IN ENGLISH LANGUAGE TEACHING: FLIPPED CLASSROOM APPROACH IN ENGLISH LANGUAGE TEACHING - Sadikova, Khurliman (Журнал иностранных языков и лингвистики, 2025)
Jon Bergmann and Aaron Sams have described this approach to instruction as a strategy where work that was ‘traditionally done in the class is now done at home, and what was traditionally homework is now completed in class’ [1; 91]. Bergmann and Sams were American high school teachers who began ‘flipping’ their chemistry classes in 2007. They recorded their explanatory lectures so that students could watch these at home, and the students then spent their classroom time working together on practical problems. The term ‘flipped learning’ is used almost interchangeably with the term ‘flipped classroom’. Flipped learning typically involves watching videos online before students come to class, therefore it may also be considered a form of blended learning